The circular economy as an alternative towards a new model for sustainable industrial activity - Marcelino-Aranda, Mariana (2022)
The linear economy model in which products are purchased, used, and thrown away, has caused excessive use of natural resources, soil, air, and water pollution due to excessive waste. On the other hand, the circular economy poses a different way to use natural resources and maintain economic activity. This document seeks to describe and analyse the conceptual basis of the circular economy. We review the information on the subject taken from high-impact databases and its role in sustainable industrial activity. Over the past two decades, the circular economy and related lines of thought have gained more significant interest in the industry, academia, and at the government level. The circular economy focuses on shifting the environmental pressure of economic growth. It promotes production systems based on waste reduction and optimization of natural resource utilization. Using products and services in loops by closing product life cycles helps lead towards regenerative development and, therefore, social and economic well-being with global impact. The European Union and China have implemented the circular economy at the micro, middle, and macro level. The circular economy provides a viable alternative to replace the linear model of economics.